Identifikasi Penyebab Abnormality Jarak Antar Step pada Eskalator Boarding Lounge Gate E3 Terminal 2 di Bandar Udara Internasional Soekarno-Hatta - Kurniawati, Zulina; Astuti, Annisa Puji; Nugroho, Rafid Rizky; Apriliansa, Muhamad Rafi; Andriansyah, Ricky; Putra Alief, Muhammad Tezza (Jurnal Teknik Mekanikal Bandar Udara, 2023)
This study aims to analyze the causes of the distance between steps abnormality on the Boarding Lounge Gate E3 Terminal 2 escalator at Soekarno-Hatta International Airport and to find out the steps that must be implemented in overcoming this problem. The research methodology used is a qualitative method in which the author collects data through field research (field research) of the object under study to obtain the required data. Data collection techniques using 3 methods, namely: observation method, interview method, and documentation method. The results of this study were found to be abnormal conditions in the step distance on the escalator Boarding Lounge Gate E3 Terminal 2. Based on the Elevator and Escalator Test Module of The Public Works Department the normal step distance is 4-5 mm. Meanwhile, based on case studies in the field, the results were 7.93 and 13.79 mm.